Risk factors for pulmonary infection after diagnostic bronchoscopy in patients with lung cancer - Shimizu, Takahiro (Nagoya J Med Sci, 2020)
Pulmonary infection is a relatively rare but serious complication of flexible bronchoscopy. The aim of this study was to identify the risk factors for pulmonary infectious complications after diagnostic bronchoscopy in patients with lung cancer. We retrospectively analyzed the medical records of 636 patients who underwent bronchoscopic biopsy for lung cancer diagnosis between April 2011 and March 2016. We compared patients’ characteristics, chest computed tomography and bronchoscopic findings, undertaken procedures, and final diagnoses between patients who developed the complication and those who did not. Pulmonary infection after the diagnostic bronchoscopy occurred in 19 patients (3.0%) and included pneumonia in 16 patients and lung abscess in 3. Patients with larger lesions, presence of endobronchial lesions, histology of small cell lung cancer, and advanced disease stage tended to develop pulmonary infectious complications more often. Our multivariate analysis revealed that a larger lesion size and the presence of endobronchial lesions were independently associated with post-bronchoscopy pulmonary infection. Although we found no mortality associated with the infections, two patients were left with significant performance status deterioration after the pulmonary infection and received no anticancer treatment. In conclusion, endobronchial lesions and a larger lesion size are independent risk factors for the incidence of infections following bronchoscopic biopsy in patients with lung cancer.